Occurrence of endophytic bacteria of the genus Azospirillum in lowland rice plants collected in Santa Catarina state (Revista de Ciências Agroveterinárias, 2010)
Bacteria of the genus Azospirillum can endophytically colonize lowland rice plants and contribute to the development of this culture. The objective of this work was to evaluate the occurrence of endophytic Azospirillum spp. isolated from roots and stems of lowland rice plants grown in the State of Santa Catarina, Brazil. Samples of lowland rice plants were collected in eight farms in the cities of Guaramirim (two areas), Massaranduba, Rodeio (two areas), Rio do Sul, Agronômica and Pouso Redondo. Azospirillum spp. occurrence in disinfested roots and stems of the collected plants was evaluated using the More Probable Number method (MPN), in two semi-solid selective broth: NFb (A. lipoferum and A. brasilense) and LGI (A. amazonense), and the similarity among the eight areas was estimated by the principal component analysis (PCA). The bacteria grown in semi-solid broths were purified in their respective broths, isolated in PDA broth to obtain pure and morphologically characterized cultures. The mean population density of Azospirillum spp. varied from 1.6x108 to 1.42x108 cells g-1 of fresh matter (LGI), and from 1.76x108 to 1.56x108 cells g-1 of fresh matter (NFb), in roots and stem, respectively. Sixty two (62) isolates were obtained, most of them from disinfested roots. The results showed that Azospirillum spp. occurs in satisfactory population densities in lowland rice fields in Santa Catarina and can be found colonizing roots and stems of rice plants.
Keywords: Oryza sativa; Endophytic colonization; Plant growth-promoting bacteria.